2009
DOI: 10.3382/ps.2009-00063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irradiation on foaming properties of egg white proteins

Abstract: To investigate the effects of irradiation on structural and functional properties of egg white proteins, which enhance foaming ability, egg white was separated and irradiated at doses of 0, 2.5, and 5 kGy. The foaming ability of egg white was increased, whereas foam stability was decreased by irradiation. Turbidity and protein oxidation of egg white was increased by irradiation with an increase of irradiation dose. The content of free sulfhydryl and disulfide was not affected by irradiation. According to 2-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 18 publications
5
35
0
1
Order By: Relevance
“…However, irradiation can also cause significant changes in functional properties of egg white due to the oxidation of egg components by hydroxyl radicals produced through the radiolysis of water (Branka et al, 1992;Min et al, 2005). Free radicals can cause fragmentation, aggregation, and cross-linking of protein molecules, and induce changes in physicochemical and functional properties such as viscosity, foaming, binding, emulsification, thermal gelation, and thickening properties of egg white (Ma et al, 1993;Moon and Song, 2001;Liu et al, 2009). Changes in physicochemical and functional properties of egg white can significantly infiuence the quality of many food products using egg as an ingredient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, irradiation can also cause significant changes in functional properties of egg white due to the oxidation of egg components by hydroxyl radicals produced through the radiolysis of water (Branka et al, 1992;Min et al, 2005). Free radicals can cause fragmentation, aggregation, and cross-linking of protein molecules, and induce changes in physicochemical and functional properties such as viscosity, foaming, binding, emulsification, thermal gelation, and thickening properties of egg white (Ma et al, 1993;Moon and Song, 2001;Liu et al, 2009). Changes in physicochemical and functional properties of egg white can significantly infiuence the quality of many food products using egg as an ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, other studies (Huang et al, 1997;Serrano et al, 1997) indicated that low-dose irradiation (1.5 to 2.5 kGy) did not cause substantial changes in physicochemical and functional properties of shell eggs and egg products. Some researchers (Ma et al, 1993;Liu et al, 2009;Song et al, 2009) suggested that the foaming properties of egg white can be improved by low-dose irradiation (1 to 5 kGy).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the decrease in the viscosity of egg white by irradiation will improve flow of liquid egg white or liquid whole egg, which could be highly useful for egg processing. Liu et al (2009) detected an increase in the foaming ability of egg white irradiated at doses of 2.5 and 5 kGy, whereas foam stability was decreased by irradiation. Turbidity and protein oxidation of egg white was increased with the increasing irradiation dose.…”
Section: Microbiological Safety and Nutritional Adequacymentioning
confidence: 93%
“…Foaming ability is related to the rate at which the surface tension of the air-water interface decreases (Liu et al, 2009). …”
Section: Foaming Propertiesmentioning
confidence: 99%
“…Radicals cause protein changes still not well understood, which are attributed to protein fragmentation (Liu et al, 2009), or even crosslinking (Ali et al, 2011). Clark et al (1992 reported on the improved functional properties in gamma-irradiated spray-dried egg white while Ma et al (1990) reported an increase in surface hydrophobicity in egg white upon γ- Thus, Forsythe (1957) indicated that small amounts of fat in the sample decreased the FA and FS of eggs, and the yolk contains around 30-40 % of lipids on a solids basis (Marion, Woodroof and Cook, 1965;Chung and Stadelman, 1965).…”
Section: Foaming Propertiesmentioning
confidence: 99%